(untitled) (Bangladesh Pharmaceutical Journal, 2015)
Simple, precise and sensitive extractive spectrophotometric methods have been developed for the determination of domperidone in pharmaceutical formulations. The new methods involve the formation of colored extractable ion pair complexes of the drug with bromothymol blue (BTB) and bromophenol blue (BPB) in acidic medium. The effects of various parameters like pH, reagent concentration and shaking time were studied. The extracted complexes of domperidone showed maximum absorbance at 410 nm with BTB and at 415 nm with BPB dye. The stiochiometry of the reaction between domperidone, BTB and BPB was found to be 1: 4. Domperidone was found to obey Beers law in the concentration ranges of 0.6-35 ?g/ml, 1-30 ?g/ml with BTB and BPB, respectively. The method has been applied successfully for the determination of domperidone in commercial tablets and suspension samples. The results obtained by the proposed methods were validated statistically and compared with the official HPLC method. DOI: http://dx.doi.org/10.3329/bpj.v17i1.22310 Bangladesh Pharmaceutical Journal 17(1): 25-31, 2014